KURIKULUM DAN PENGEMBAGANGAN KURIKULUM SECARA ONTOLOGIS, EPISTIMOLOGIS DAN YURIDIS - Sukatin; Muammar Qaddafi; Juanda Khalimatun Nuha; Muhammad Habibi (As-Sulthan Journal of Education, 2025)
In Indonesia, the development of its educational curriculum is based on the philosophical foundation of Pancasila as the state ideology, which essentially serves as a medium for the transfer and realization of Pancasila values into educational practice and learning. The main mission and position of educators are to instill, form, fill, develop, expand, refine, and pass on cultural values, knowledge, morals, attitudes, skills, and technology to students and society. To meet the above demands, Indonesia has continuously developed its educational curriculum over time, supplemented by supporting tools such as mastery of various facts, concepts, principles, norms, ideas, procedures, and various scientific abilities, as well as various life skills, both written and digital, which exist within the context of learning literacy. The development and formulation of this curriculum depend on state policies that continuously adapt to global developments and changes.